Aptamers as a promising approach for the control of parasitic diseases - Ospina-Villa,Juan David (2016)
ABSTRACT Aptamers are short single-stranded RNA or DNA oligonucleotides that are capable of binding various biological targets with high affinity and specificity. Their identification initially relies on a molecular process named SELEX (Systematic Evolution of Ligands by EXponential enrichment) that has been later modified in order to improve aptamer sensitivity, minimize duration and cost of the assay, as well as increase target types. Several biochemical modifications can help to enhance aptamer stability without affecting significantly target interaction. As a result, aptamers have generated a large interest as promising tools to compete with monoclonal antibodies for detection and inhibition of specific markers of human diseases. One aptamer-based drug is currently authorized and several others are being clinically evaluated. Despite advances in the knowledge of parasite biology and host-parasite interactions from "omics" data, protozoan parasites still affect millions of people around the world and there is an urgent need for drug target discovery and novel therapeutic concepts. In this context, aptamers represent promising tools for pathogen identification and control. Recent studies have reported the identification of "aptasensors" for parasite diagnosis, and "intramers" targeting intracellular proteins. Here we discuss various strategies that have been employed for intracellular expression of aptamers and expansion of their possible application, and propose that they may be suitable for the clinical use of aptamers in parasitic infections.